A CRITICAL ANALYSIS OF THE SERRATED FLOW OF PORTEVIN - LE CHATELIER EFFECT (Sciences & Technology. A, exactes sciences, 2000)
Plastic instabilities associated with the Portevin - Le Chatelier (PLC) effect will be examined with special attention to relaxation oscillations behaviour. The types of serrations are studied and interpreted in terms of a constitutive flow model which takes into account stress dependent changes accompanying a strain rate changes. The experimental data in aluminium - magnesium industrial dilute alloys are discussed in the light of the present study and a new analysis vision of PLC effect is proposed. Emphasis is put on the connection between the different types of instabilities and the relaxation oscillations behaviour. The spatial correlation in the case of A and B types of PLC instabilities is investigated and discussed with reference to A9G5 alloy.